OPPORTUNITIES FOR EXTRACURRICULAR EDUCATIONAL WORK HIGHER EDUCATIONAL INSTITUTION IN THE FORMATION OF COMMUNICATIVE CULTURE FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2007)
At this article is considered components of educational work of university and so its possibilities on a way of forming of communicative culture of students.